Pemberlakuan Fiqih Keluarga Bagi Minoritas Muslim: Masalah Keabsahan Perkawinan Poligami di Australia dan Thailand - Ahmad Faridz Anwar (CV. Strata Persada Academia, 2023)
In countries with a Muslim majority, the application of Family Fiqh often does not pose a problem, as the majority of the society adheres to and comprehends the principles set forth in Islamic teachings. However, in countries with a non-Muslim majority, such as Australia and Thailand, minority Muslims are often confronted with challenges in applying the Family Fiqh principles they adhere to. One of the arising issues is the validity of polygamous marriages. This study focuses on the validity of polygamous marriages in Australia and Thailand. The research method deemed suitable for this composition is a descriptive qualitative approach. In Australia and Thailand, polygamy is prohibited under national law in those countries. Therefore, Muslim minorities in those countries must comprehend the national legal regulations prior to entering into polygamous marriages and consider the legal implications of such decisions.